2000
DOI: 10.1089/acm.2000.6.499
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Cohort Trial ofEuphrasiaSingle-Dose Eye Drops in Conjunctivitis

Abstract: Euphrasia single-dose eye drops can effectively and safely be used for various conjunctival conditions by general practitioners and ophthalmologists. A dosage of one drop three times a day seems to be the general prescribed dosage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 14 publications
2
18
0
2
Order By: Relevance
“…Columns and bars show the mean±standard deviation (n=3). *p≤0.01 -culture of corneal cells treated with plant extracts compared to the non-treated culture control substances of the Euphrasia herb include iridoglicozoids (aucubin), tannins, phenolic acids, etheric oils, resin substances and flavonoids (2,5,18,19).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Columns and bars show the mean±standard deviation (n=3). *p≤0.01 -culture of corneal cells treated with plant extracts compared to the non-treated culture control substances of the Euphrasia herb include iridoglicozoids (aucubin), tannins, phenolic acids, etheric oils, resin substances and flavonoids (2,5,18,19).…”
Section: Figmentioning
confidence: 99%
“…Therefore, they may be potentially used in therapeutic supplementation, e.g. in ocular inflammation (2,5). It has been shown that flavonoids and polyphenols possess an inflammation reducing effect.…”
Section: Figmentioning
confidence: 99%
“…A dosage of one drop three times a day seems to be the general prescribed dosage. It was published in the Journal of Alternative and Complementary Medicine in 2000 [5].…”
Section: Homeopathy and Viral Conjunctivitismentioning
confidence: 99%
“…• Eyebright (Euphrasia officinalis) eye drops have been found to be effective in a trial for various conjunctival conditions (Stoss et al 2000). makes a good wash for both eyes, using clean cotton wool for each eye.…”
Section: Herbal Treatment Of Childrenmentioning
confidence: 99%